Characteristics of convective vortices and dust devils at gale crater on Mars during MY33. (April 2022) - Uttam, Shefali; Sheel, Varun; Singh, D.; Newman, C.E.; Lemmon, M.T.
Abstract: Convective vortices that are dust laden (dust devils), are believed to be an efficient mechanism for particle entrainment in the Martian atmosphere. Such vortices can be identified in-situ by landers or rovers by the reduced surface pressure when they pass by the instrument. We analyse data from the Rover Environmental Monitoring Station (REMS) on-board the Mars Science Laboratory (MSL) rover Curiosity during mission sols 1019 to 1686 (corresponding to Martian Year (MY) 33). We identified 611 short pressure drops that likely indicate the passage of convective vortices in vicinity of the rover. The cumulative power-law analysis of the detected pressure drops suggests a low abundance of stronger pressure drop events at the MSL site as compared to the Pathfinder and Phoenix sites. The reason for this can be attributed to the smaller boundary layer height at Gale crater. The power-law slope is smaller for MY 33 as compared to previous years, suggesting that the dust devil activity also increased inside the Gale crater with the progressing year. Among all vortices detected, 63 vortices (∼10%) also show a simultaneous drop in ultraviolet intensity, which signifies obscuration of sunlight by the dust-laden vortices. A seasonal study for dust devils occurrences based on UV flux data shows an increase in their frequency during the local southern summer season. A majority of our estimated tangential wind velocities are well below the Martian dust lifting threshold. This indicates that either the vortices passed far from the measuring instrument or that the threshold being used is higher than the actual threshold on Mars. Highlights: We provide a correlation between the power-law slopes of different missions and the height of the PBL at those locations. We investigate the seasonal variation of dust devils using the data of a UV-logger on board MSL rover in Gale crater on Mars. We provide a comparison of the seasonal variation of dust lifting vortices and the DDA as calculated by MarsWRF model. We predict that vortices in Gale crater are less capable of lifting dust as compared to its Earth counterpart.